Cosmography and/in the Academy: Authorizing the Ideological Pathways of Empire. (2nd January 2023) - Mehdizadeh, Nedda
ABSTRACT: This article examines how the study of premodern cosmographical knowledge in the modern classroom can educate students about how knowledge is made. Through my discussion of a course unit that considers Richard Hakluyt's Principall Navigations (1589) in conversation with Sebastian Münster's Cosmographia (1544), I demonstrate how these premodern visions of the world created ideological pathways toward imperial and racial violence. White, European cosmographers developed a genre of knowledge production about the world, and these generic conventions both authorized their perspectives and established a conceptual mapping toward empire that early modern cartographers and travel writers would reproduce and expand. These cosmographers, cartographers, and travel writers utilized these conventions to legitimize their visions of the world. I argue that these ideological pathways extend the theoretical and empirical work of these writings into course curricula, and continue to inform how knowledge is produced.